Our earth : the ultimate reference resource for the whole family, with over 500 photographs and illustrations. (Bath : Parragon, 2013)
Welcome to Our Earth. This beautifully illustrated family reference guide includes fantastic colour illustrations and is a comprehensive guide to our planet, its structure and systems and its place in the solar system. With annotated 3D illustrations and cut-away diagrams, every page is brought to life. Here is your key to unlock the secrets of our planet and the universe. Explore our incredible planet, its geology,rocks,natural phenomena,climate and plants. Our Earth has five sections, each written by experts in a clear,informative style,and includes: Our Solar System,Geology and Formation, The Power of Nature, A World of Plants, and Weather and Climate.
Includes index.
Keywords: Earth (Planet) -- Juvenile literature